Challenges in Learning a Foreign Language in Three Philippines Higher Education Institutions - Aguilar, Mark Gabriel; Rebolla, Marilyn (Universitas Jambi, Magister Program of English Education Department, 2023)
Learning a foreign language is required in some degree programs given its perceived significance in some industries and to the employability of graduates, however, literatures suggest that students commonly experience difficulties in learning a foreign language; in fact, many studies have already determined factors that cause this. On the other hand, despite its importance, it is noticeable that although it is well researched in many countries, this topic seemed to have failed to catch the attention of many researchers in the Philippines. It was also observed that alongside the dearth of studies, each of the few studies were limited to one educational institution, resulting in the absence of a comprehensive study on this topic, which raises the need to conduct one that will cover a broader scope. Applying a descriptive research design and a quantitative research approach, this research aimed to determine the specific aspects of Nihongo language learning that pose challenges for students in selected educational institutions. Additionally, the research examines if there are differences in the perception of students and their sexuality. By identifying the specific challenges faced by students in learning Nihongo, educators and institutions can develop more effective teaching strategies and support systems to address these challenges. Additionally, understanding the potential influence of students' sexuality on language learning experiences can lead to a more inclusive learning environment. Ultimately, the outcomes of this study have the potential to enhance the quality of Nihongo language education and improve students' overall learning experiences in Philippine higher education institutions.